Aksiologi Pengembangan Kurikulum Pembelajaran Bahasa Arab di Madrasah Tsanawiyah Darul Hikmah Tawangsari Tulungagung - Nurcholis, Ahmad; Harianto, Budi; Zain, Biqi Asshafah (LP3M Universitas Islam Zainul Hasan Genggong, 2020)
The axiology of learning Arabic is the essence of the benefits contained in learning Arabic. The purpose of this study was to determine the functions and benefits of Arabic Language Curriculum Development, Suitability of Arabic Language Curriculum Development with Vision and Mission, Problematic Development of Arabic Language Curriculum in Darul Hikmah MTs. The method and design in this research is a qualitative approach with the type of research used is descriptive. The results showed that the Axiology of the Development of Arabic Language Curriculum in Madrasas is the use of Arabic Language in learning and habituation of Language (Bi’ah Lughowiyah) as oral and written communication. Through the development of the curriculum, the axiology is considered to have the usefulness and benefits in understanding the Qur’an, hadith and Arabic texts. The development of Arabic Language Curriculum in MTs DH is adjusted to the Vision and Mission of character building and noble character through the habituation of language (Bi’ah Lughowiyah) in learning and in the Madrasah environment. The problematic of developing curriculum at Madrash is in terms of the number of teachers who have not participated in curriculum development, some of the management of OPPM and KMI Curriculum Staff in the application of Language Habituation. While other inhibiting factors are the diversity of students’ backgrounds, internal motivation of students, violations, discipline, and Arabic are still considered not important for students and the problem of habituating Arabic language that does not pay attention to aspects of Grammatical Language.